Continuous local material model for the mechanical stress-dependency of magnetic properties in non-oriented electrical steel. Issue 4 (1st July 2019) - Karthaus, Jan; Elfgen, Silas; Hameyer, Kay
Abstract : Purpose: Magnetic properties of electrical steel are affected by mechanical stress. In electrical machines, influences because of manufacturing and assembling and because of operation cause a mechanical stress distribution inside the steel lamination. The purpose of this study is to analyse the local mechanical stress distribution and its consequences for the magnetic properties which must be considered when designing electrical machines. Design/methodology/approach: In this paper, an approach for modelling stress-dependent magnetic material properties such as magnetic flux density using a continuous local material model is presented. Findings: The presented model shows a good approximation to measurement results for mechanical tensile stress up to 100 MPa for the studied material. Originality/value: The presented model allows a simple determination of model parameters by using stress-dependent magnetic material measurements. The model can also be used to determine a scalar mechanical stress distribution by using a known magnetic flux density distribution.